Smart monitor of pacemaker patient by using IoT cloud in real time - Jameel Kadhim Abed; Hassnaa Mustafa Abd-aljabar (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
People severing from heart diseases are increasing day after day, now it's more important to focus on this destructive problem and provide a good health care and remote patient monitoring .An effective monitoring system has been discovered to monitor patients who are implanting a pacemaker and need long-term follow-up. So extensive research has been done to monitor ECG and analyze it by using the free open source website and linking it with portable ECG system that are responsible for the presentation and storage of data to the doctor and patient. In this research we will develop a new method of ECG monitoring for patients who are implanting pacemakers and help them to transfer their ECG signal for long distances depending on the Internet things (IOT). Once the device is worn, it will start collecting ECG information and sent it directly via Wi-Fi to the IOT cloud. Reviewing ECG data through the web has led to the alleviation of the problem of the inability of the doctor to monitor the patient from the home as well as in the event that the doctor is being in another country ,the device also helps to discover the magnetic field that confuses the pacemaker by giving the patient a warning. The results of the test are able to detect that the system would be reliable for displaying real-time ECG data, which could help facilitate patient follow-up after implantation of the pacemaker at home with ease of use and cheaper price.